Differential Expression Profile of lncRNA in Glioma Cells and the Effect of lncRNA NKX3-1 on Glioma Cells Through Fem1b/SPDEF Pathway - Cai, Yang; Wang, Ming; Cui, Yan; Tan, Zhigang; Jiang, Yugang (Frontiers in Oncology, 2021)
Objective To investigate the differential expression of lncRNA in glioma cells, as well as the effect of lncRNA NKX3-1 on glioma cells. Methods Glioma-related data were first downloaded from the TCGA database and analyzed using bioinformatics, after which the lncRNA NKX3-1 was chosen for further experiments. The expression of the lncRNA NKX3-1 in glioma tumor samples was detected using qRT-PCR. The subcellular localization of lncRNA NKX3-1 was determined using fluorescence in situ hybridization (FISH). CCK-8, flow cytometry, cell scratch, and transwell assays were used to detect cell proliferation, apoptosis, and invasion. The downstream pathway of lncRNA NKX3-1 was investigated using luciferase assays and detected using western blot, transwell, and cell scratch assays. Results The differential expression profile of lncRNA in glioma was obtained. NKX3-1 lncRNA was found to be significantly increased in glioma tumor tissues. LncRNA NKX3-1 was found in the nucleus. Proliferation, invasion, and migration of glioma cells were significantly increased (P <0.05) in the lncRNA NKX3-1 overexpression group, while apoptosis ability was significantly decreased (P <0.05). Tumor volume and weight were significantly increased in the lncRNA NKX3-1 overexpression group in nude mice (P <0.05). LncRNA NKX3-1 significantly increased the luciferase activity of Fem1b 3’-UTR-WT reporter genes (P <0.05) as well as the levels of SPDEF protein (P <0.05). The protein level of FEM1B was significantly reduced. Cell invasion and migration were significantly increased (P <0.05) in the lncRNA NKX3-1 overexpression group plus SPDEF group. Conclusion We investigated the differential expression profile of lncRNAs in glioma and discovered that the lncRNA NKX3-1 plays an important role in cancer promotion via the Fem1b/SPDEF pathway.